Use of Trichoderma for disease control, development and growth stimulus in Lactuca sativa L. - Schwab, Natalia Teixeira; Buffon, Paola Ana; Silva, Daniel Conte; Rampazzo, Jonatas Catapan; Führ, Airton; Kreimeier, Felipe (Acta Iguazu, 2019)
The current pressure for healthy food implies in use of alternative methods to the conventional use of agrochemicals. In this scenario, the biological control is fundamental for food safety. The use of Trichoderma to control of diseases in lettuce appears as a viable alternative. The objective of this work was to verify the efficiency of Trichoderma to control diseases in lettuce and to evaluate its influence in the stimulus of development and growth of this crop. Six treatments were used: T1 = control; T2 = application of Trichoderma in liquid formulation at intervals of 7 days; T3 = application in liquid formulation at 14 days intervals; T4 = application in granulated + liquid formulation at intervals of 7 days; T5 = application of granulated + liquid formulation at 14 days intervals, and T6 = application of Trichoderma in granulated formulation only in planting. The final number of leaves (NFF), phyllochron (°Cday.leaf-1), fresh mass and diameter were evaluated and was observed the occurrence of diseases in the different treatments. The results indicate that the application of Trichoderma is recommended for the control of Sclerotinia sclerotium on lettuce but does not promote significant increases in the development and growth of plants.